Reforming Indonesia’s OJK to Comply with International Standards: Lessons from Australia - Agus, Riyanto; Santoso, Budi; Paraningtyas, Paramitha (Brawijaya Law Journal, 2023)
This research examines the need to reform the supervisory model of the Financial Services Authority (OJK) to align with international supervisory standards, such as the Basel Accords and IOSCO's principles. In Indonesia, the supervisory model used is an integrated one, where OJK is the sole authority responsible for supervising the financial services sector, but it shows weaknesses because the scope of supervision is too broad and therefore unfocused. This study begins with the hypothesis that it is time to move to an alternative model of OJK supervision by learning from supervisory models in other countries. It begins by examining international supervisory standards and their relevance to the context of OJK supervision, exploring specific provisions in the standards that relate to the scope of this paper. The method used is a micro comparison by comparing the supervisory models in Indonesia and Australia. In Australia, the prevailing supervisory model is Twin Peaks, which separates the task of maintaining financial system stability from the task of maintaining market behavior and consumer protection more clearly. Lessons learned from the Australian model in relation to coordination and cooperation, accountability and governance, and outcomes, provide valuable insights and form the basis of contextual recommendations for future OJK reforms. These recommendations aim to ensure that the OJK fully supervises to global standards to address the weaknesses and challenges identified in the integrated model. Accountability and governance, as well as the outcomes achieved, provide valuable insights and inform recommendations for future reform of the OJK.